Altered glutamatergic neurotransmission in the striatum regulates ethanol sensitivity and intake in mice lacking ENT1 - Chen, Jihuan (2010)
Alcohol-sensitive type 1 equilibrative nucleoside transporter (ENT1) regulates adenosine-mediated glutamate neurotransmission in the brain. Our behavioral studies suggest that the diminished aversive effects of ethanol and the increased resistance to acute ethanol intoxication in mice lacking ENT1, could be related to increased voluntary ethanol self-seeking behavior. In addition, we found that ENT1 null mice were resistant to the ataxic effects of glutamate antagonists when tested on a rotarod. Using microdialysis experiments, we examined glutamate levels in the dorsal and ventral striatum in response to ethanol. In the dorsal striatum of ENT1 null mice, a low intoxicating dose of ethanol (1.5 g/kg) induced a greater increase of glutamate levels, while a higher hypnotic dose of ethanol (3.0 g/kg) decreased to a lesser degree the glutamate levels, compared with that of wild-type mice. In the ventral striatum, however, the low (1.5 g/kg) and the high (3.0 g/kg) ethanol doses altered glutamate levels similarly in both genotypes. Our results suggest that adenosine-regulated glutamatergic signaling contributes to a reduced level of alcohol response, which might be associated with a higher susceptibility for alcoholism in humans.